Shaping Gender Policy in Turkey : Grassroots Women Activists, the European Union, and the Turkish State - Aldikaçti Marshall, Gül (Book collections on Project MUSE., 2013)
This book is an analysis of the ways in which women grassroots activists, the European Union, and the Turkish state are involved in shaping gender policies in Turkey. The author uncovers how, why, and to what extent Turkish women, in addition to the Turkish government and the European Union, have been active in developing and implementing policy changes. Through analysis of the role of multiple actors at the subnational, national, and supranational levels, the author provides a detailed account of policy diffusion and feminist involvement in policymaking. Contextualizing the meaning of gender equality and multiple approaches to women's rights, she highlights a pivotal but neglected dimension of scholarship on Turkey's candidacy for European Union membership. This book provides a multilevel analysis of gender policy in a predominantly Muslim country, and highlights Turkey's role at a time of swift structural changes to several political regimes in the Middle East.